Pengelolaan Sektor Perkebunan Kelapa Sawit dari Perspektif Program Kepedulian Sosial di Kecamatan Kamipang Kabupaten Katingan - Leda Almuqsith; Kartiansyah Kartiansyah (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2017)
This study aims to determine the impact of the existence of palm oil plantations on the socio-economic conditions of the people in Kamipang District, Katingan District. The type of data used in this study is secondary data obtained from BPS, Sub-District Offices, village/district, and the private sector and primary data obtained directly from different respondents in Kamipang Subdistrict to determine the number of samples used by purposive sampling technique or sampling. intentionally that is equal to 20% of the total population or as many as 30 respondents. The results of the study show that the management of oil palm plantations has an impact on social conditions that are very influential, namely after the existence of the oil palm plantation company PT Arjuna Utama Sawit. The impact is such as access to education in Kamipang Subdistrict, new economic activities such as lodging, restaurants, crossing services, and salons. After the existence of a coconut plantation company, PT. Arjuna Utama Sawit, those who were previously less prosperous are now more prosperous. They arrived at zero economic conditions, the impact of the existence of a sick coconut plantation company, PT. Arjuna Utama Sawit for economic conditions greatly affects that is after the existence of oil palm plantation companies PT. Arjuna Utama Sawit compared to the existence of a plantation company PT. Arjuna Utama Sawit.